NEW WHEATS FOR MEXICO - RUPERT, J; HARRAR, JG; BORLAUG, NE (Hospital General, CD MEXICO, DF, MEX, 1900)
Mexico now produces approx 50-60% of the wheat it consumes The cost of wheat imported (11,000,000 bu) during 1947 was $120,000,000 (pesos), by far the largest expenditure for food imports Wheat is grown under a wide range of soil and climatic conditi
PHYS REV B
Keywords: WHEATS, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL